التاريخي والمتخيل في رواية « الصلصال» لـ « سمر يزبك » - نورهان خلايفية (My University, 2024)
HistoryisconsideredoneofthemostimportantnarrativefoundationsthatwasstronglyprohibitedinSamarYazbek’snoveltitledClay, asthewriterreliedonittoconveyherintentionas a resultofthisartisticpresentationoftheSyrianissue, whichinturnextendsbacktoancienttimes, asifsheistryingtoconfirmthathistoryrepeatsitself, andthisiswhatdepriveshumanity. Stabilityandtranquility, andallofthiscameinanimaginativewayindrawingtheeventsandtheirrelationshipwiththepeople, timeandplacethatframethegeneralframeworkinwhichtheeventsrelatedtothehistoryofSyriamove. Thewriterworkedtoinvokethisimaginedhistoryinordertorevealitstruth, whichtheotherworkedtodistortanddistort, andperhapsthemostprominentfactscontainedinThisnovelisthetruthabouttheSyrianrevolution, whichgrantedthetraitorstherightandthuswastedtherightsofthepeasantswhoshoulderedtheresponsibilityfortherevolution. Inshort, thisnovelwas a criticismofthebitterrealityinwhichSyriaisfloundering, byreturningtotheembraceofhistory, andherethetechniqueofrecallinghistoryformed a linkforcommunication. Betweenthepastandthepresent, consideringthatthepresentisonly a logicalextensionofthepast, anditsquestioningofhistoryreflectsthefactthatitisanopencalltore-readhistorywith a criticaleyeandthusnotsurrendertothefactscontainedinthebooks. Thenovelrepresents a catalystforawarenessthattargetsthereader, whoisconsidered a pillarofcreativeworksothathecantakeHehasthetaskofresearchingandquestioningthehistoricalfactsthateveryonehasworkedtofoldasbooksarefolded, andallofthisisbecausetheirappearancemayhindertheirauthoritarianinterests, whichwillcontinuetocarrythesamesecretthroughouttime, butnothingwillremainasitisbecausehistorywillinevitablyimposeitselfbecauseitdoesnotdieorend. Thisisthepurposeforwhichrealhistoryismixedwiththeimaginedinthisnovel, becausethepurposeistorefutewhathistoryhasbroughtaboutintermsof a proposaldifferentfrom a realitythatthewritersawastheexclusivedomainofpeoplewhoweremarginalizedbyothers, inordertoshowthedualityofslaveandmaster. Despiteallthis, thepastremainstheonlywaytodrawfeatures. Thepresentandthefuture -------------------------- يعتبر التاريخ من أهم المرتكزات الروائية التي حظرت بقوة في رواية سمر يزبك الموسومة بالصلصال، إذ اعتمدت عليها الكاتبة في إبلاغ مقصديتها من جراء هذا الطرح الفني للقضية السورية التي تمتد بدورها إلى قديم الزمان، وكأنها تحاول التأكيد على أن التاريخ يعيد نفسه، وهذا ما يحرم الإنسانية الاستقرار والطمأنينة، وكل هذا جاء بطريقة متخيلة في رسم الأحداث وعلاقتها بالشخوص والزمان والمكان المؤطرين للإطار العام الذي تتحرك فيه الأحداث المتعلقة بتاريخ سوريا، حيث عملت الكاتبة على استدعاء هذا التاريخ المتخيل قصد كشف حقيقته التي عمل الآخر على تشويهها وتحريفها، ولعل أبرز الحقائق التي وردت في هذه الرواية حقيقة الثورة السورية التي منحت للخونة الحق وبالتالي أهدرت حقوق الفلاحين الذين حملوا على عاتقهم مسؤولية الثورة، ومجمل القول أن هذه الرواية كانت بمنزلة انتقادا للواقع المرير الذي تتخبط فيه سوريا وذلك من خلال العودة إلى أحضان التاريخ، وهنا شكلت تقنية استدعاء التاريخ همزة وصل للتواصل بين الماضي والحاضر على اعتبار أن الحاضر ما هو إلا امتداد منطقي للماضي ، كما أن مساءلتها للتاريخ تعكس حقيقة مفادها دعوتها المفتوحة لإعادة قراءة التاريخ بعين ناقدة وبالتالي عدم التسليم للحقائق التي تستبطنها الكتب، فالرواية تمثل باعثا للوعي الذي يستهدف القارئ الذي يعد ركيزة للعمل الإبداعي حتى يأخذ على عاتقه مهمة البحث والتساؤل عن الحقائق التاريخية التي عمل الكل على طيها كما تطوى الكتب وكل هذا لأن ظهورها قد يعيق مصالحهم السلطوية التي ستظل حاملة لنفس السر على مر الأزمنة، لكن لا شيء سيظل على حاله لأن التاريخ سيفرض نفسه لا محالة لأنه لا يموت ولا ينتهي، وهذا هو الغرض الذي امتزج لأجله التاريخ الحقيقي مع المتخيل في هذه الرواية، لأن المُراد هو تفنيد ما أتى به التاريخ من طرح مغاير لواقع رأته الكاتبة حكرا على أناس هُمشوا من قبل آخرين لتظهر ثنائية العبد والسيد، ومع كل هذا يبقى الماضي السبيل الوحيد لرسم ملامح الحاضر والمستقبل -------------------------
Keywords: History - the imaginary - the historical imaginary - the Syrian revolution - experimentation - recalling history; التاريخ- المتخيل- المتخيل التاريخي- الثورة السورية- التجريب- استدعاء التاريخ.: Histoire - l'imaginaire - l'imaginaire historique - la révolution syrienne - l'expérimentation - la remémoration de l'histoire.